Nature-based climate adaptation projects, their governance and transitional potential-cases from Copenhagen - Jørgensen, Gertrud; Fryd, Ole; Lund, Anna Aslaug; Andersen, Peter Stubkjær; Herslund, Lise (Frontiers in Sustainable Cities, 2022)
This paper investigates and broadens the discussion of nature-based climate adaptation for stormwater management and coastal flooding. Based on three Copenhagen cases of locally initiated innovative flagship projects and framed by governance and transition theory, we investigate how nature-based solutions can be understood in a real-life context, and how hybrid projects joining technical and nature-based solutions might work; the governance methods of such projects; and their transitional potential. The cases underscore the importance of nature perception for the design of the project, and the role of daily recreational users as crucial for project legitimacy. Innovative projects might seem local, but often they are embedded in larger strategies and serve to flesh out such strategies and might even change them in a longer perspective. New problems and projects foster a need for new types of partnerships, which can challenge co-operation. Finally, it is questioned how – and if – experiences from flagship projects can be anchored and mainstreamed into a new normal for climate adaptation.